Development Of Badminton Sports In Schools - Samadova Uktabar Hasanovna (Periodica Journal, 2024)
This article describes how to teach badminton in physical education classes, to increase students' interest in the lesson and to increase the efficiency of the lesson, as well as to teach sensitivity and agility, and the methods of correct time allocation.
Keywords: badminton; volon; racket